FC 066DICKKOPF-3 (DKK3) LINKS RECIPROCAL LUNG AND KIDNEY INJURY IN MICE AND HUMANS. (29th May 2021) - Schunk, Stefan; Beisswenger, Christoph; Sarah, Triem; Hütter, Gregor; Sarakpi, Tamim; Boor, Peter; Jörres, Rudolf; Watz, Henrik; Welte, Tobias; Vogelmeier, Claus; Gröne, Hermann; Fliser, Danilo; et al.
Abstract: Background and Aims: Chronic kidney disease (CKD) and chronic obstructive pulmonary disease (COPD) represent global public health problems with high disease-related morbidity and mortality. However, the interaction between both diseases remains unclear. Method: In a novel murine model, cigarette smoke (CS)-induced lung injury was combined with a CKD model (CS-CKD model). In 2, 314 patients of the prospective multi-center COSYCONET study, urinary Dickkopf-3 (DKK3), a renal tubular stress marker, was quantified. The association between urinary DKK3 and trajectories of FEV1 and estimated glomerular filtration rate (eGFR), exercise capacity, risk of exacerbation, and mortality was determined (follow-up 37.1 months). Results: In the CS-CKD model, CKD was associated with higher systemic and pulmonary inflammation, and the combination of CKD and CS significantly aggravated kidney inflammation as well as fibrosis and increased renal expression of DKK3. Abrogation of Dkk3 attenuated kidney injury and pulmonary inflammation alike. In COPD patients, higher urinary DKK3 was associated with rapidly declining FEV1 (OR 3.36, P<0.0001), higher risk for exacerbation, lower 6-minute walking distance, and higher all-cause mortality (HR 1.49, P=0.015). Importantly, higher urinary DKK3 was also associated with declining eGFR during follow-up (OR 2.23, P=0.0005). Neither eGFR nor proteinuria were associated with lung or kidney dysfunction during follow-up. Conclusion: In summary, the present study identified a strong pathophysiological link between lung and kidney dysfunction, which is at least partially mediated by DKK3. Urinary DKK3 allows identification of COPD patients at increased risk for deteriorating pulmonary and kidney function as well as adverse outcomes. These patients might particularly benefit from preventive therapeutic strategies as a personalized-medicine approach.